Civilian Social Support and Posttraumatic Stress Disorder Symptoms among National Guard Members - Wang, Xin; Prince, Laura; Rattan, Juhi; Swartz, Neal L.; Shukla, Vipul; Durham, Tory A.; Biehn, Tracey L.; Drue, Jennifer L.; Ramachandran, Gowri; Sutu, Christine; Benton, Amber J.; Luckoski, John L.; et al. (Translation: The University of Toledo Journal of Medical Sciences, 2018)
Increasing evidence suggests that posttraumatic stress disorder (PTSD) symptoms are highly prevalent and pervasive among National Guard members who served in recent wars. Previous meta-analyses report a lack of social support as one of the strongest risk factors for the development of PTSD symptoms. Social support among military members is typically categorized into two types: assistance and support which is received from military leaders and fellow members of one’s unit and civilian social support which is obtained from civilian family and friends. Prior research has demonstrated that unit support is associated with less severe PTSD symptoms. In addition to unit support, the influence of civilian social support was also considered a potent buffer for PTSD symptoms. Civilian social support is important to National Guard members because their experiences integrate military and civilian life more than active duty soldiers. Unlike intensive studies in active duty military personnel, fewer studies have examined the role of social support in National Guard members, and civilian social support is rarely investigated in these limited studies. This review article examines the role of civilian social support in National Guard members as a potential protective factor against the development of PTSD symptoms.